The US-China Phase One Trade Deal: An Economic Analysis of the Managed Trade Agreement - Michael Funke; Adrian Wende (Center for Economic Studies and Ifo Institute (CESifo), 2021)
In light of the recent tit-for-tat trade dispute between China and the US, interest in quantifying the effects of the so-called phase one agreement has risen. To this end, the paper quantifies the impact of the asymmetric managed trade agreement using such a multi-country open-economy dynamic general equilibrium model. Besides assessing the direct implications for China and the US, trade diversion effects are also analyzed. The model-based analysis finds noticeable positive (negative) impacts of the agreement for the US (China) as well as negative spillover effects for countries not directly affected by the managed trade deal due to trade diversion. The impact of possible future trade agreements is also examined.
Keywords: F13; F41; F42; 330; phase one deal; managed trade; open-economy dynamic general equilibrium model; United States; China